Problem Solving Skills through Mathematical Vocabulary and Formative Feedback: Evidence from Grade VII Private Schools - Maqsood, Laiqa; Sahar, Noor e; Sharjeel, Muhammad Yousuf (Annals of Human and Social Sciences, 2024)
The objective is to understand what teachers should be acquainted with to facilitate the development of problem-solving proficiency in their students. Another objective is to inquire how a teacher is informed by a comprehensive review of the research literature in mathematics education. There has been a significant focus on effective mathematics instruction.This article employs a category-based approach to examine the types of knowledge deemed essential for effective mathematical problem-solving instruction. This paper presents the findings of an action research study conducted by a teacher educator and researcher. This study sought to uncover the intentions of Grade VII school teachers. The research utilized various data sources, including reflective journals, semi-structured interviews, field notes, lesson observations, and reports. A two-stage model was proposed to guide the planning and execution of action research projects in schools. The paper concludes that formative feedback is crucial for the learning of challenging skills like problem-solving in Mathematics. It then observed their actions concerning formative feedback on midterm exams in courses that claim to teach problem-solving. The study found that action research is a highly effective approach for enhancing professional development; however, it also highlighted the challenges associated with implementing this methodology in real-world educational settings. It is essential for teachers to have a deep understanding of mathematical problem-solving, not only for their own proficiency as problem solvers, but also to guide students in developing their problem-solving skills. The study recommends that a mathematics teacher's expertise in teaching problem-solving must extend beyond their general ability to solve problems.